2012
DOI: 10.1097/ccm.0b013e3182657916
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multidimensional approach for prevention of ventilator-associated pneumonia in adult intensive care units from 14 developing countries of four continents

Abstract: The implementation the International Nosocomial Infection Control Consortium multidimensional approach for ventilator-associated pneumonia was associated with a significant reduction in the ventilator-associated pneumonia rate in the adult intensive care units setting of developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 47 publications
3
76
0
7
Order By: Relevance
“…18,48 A recent study by the International Nosocomial Infection Control Consortium (INICC) that used the CDC/NHSN diagnostic criteria (and employed intensive preventive measures) reported a 22% relative reduction in VAP; nonetheless, VAP rates remained 5 times higher than in the United States. 45 Interestingly, the INICC post-intervention rates are similar to those reported in Europe, where, until approximately 2012, public reporting of VAP was not required in many countries (Fig. 2).…”
Section: Socioeconomic Context Of Ventilator-associated Pneumonia Repsupporting
confidence: 62%
See 2 more Smart Citations
“…18,48 A recent study by the International Nosocomial Infection Control Consortium (INICC) that used the CDC/NHSN diagnostic criteria (and employed intensive preventive measures) reported a 22% relative reduction in VAP; nonetheless, VAP rates remained 5 times higher than in the United States. 45 Interestingly, the INICC post-intervention rates are similar to those reported in Europe, where, until approximately 2012, public reporting of VAP was not required in many countries (Fig. 2).…”
Section: Socioeconomic Context Of Ventilator-associated Pneumonia Repsupporting
confidence: 62%
“…99 In a contemporaneous survey of clinicians, the average duration of weaning ranged from 5 to 18 d, with the longest duration associated with synchronized intermittent mandatory ventilation combined with pressure support ventilation. 100 However, more contemporary studies have reported that the average duration of mechanical ventilation now is ϳ5-7 d. 45,46,[101][102][103] This invites speculation that the incidence of VAP likely was much greater before modern weaning and sedation practices.…”
Section: Weaning and Sedation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of preventive recommendations and monitoring of respiratory tract infections associated with mechanical ventilation is an element of surveillance in patients undergoing mechanical ventilation. These approaches decrease infection incidence, shorten hospitalisations, reduce treatment costs and improve patient safety [15,16].…”
mentioning
confidence: 99%
“…Implementation by Rosenthal et al [7] of the multi-dimensional approach to VAP of the International Nosocomial Infection Control Consortium (INICC) produced notable differences in the incidence of VAP (a 55.8% reduction) in both developed and developing countries, with rates three-to five-fold lower in health care settings with limited resources after the program was implemented. Multi-faceted approaches were the most successful, although without regular reinforcement efforts, the gains they produced were short-lived.…”
Section: Surveillance and Intervention Bundles For Ventilator-associamentioning
confidence: 99%